Flavonoid Production in Callus Cultures from Mesocarp of Stelechocarpus burahol - Habibah, Noor Aini; Moeljopawiro, Sukarti; Dewi, Kumala; Indrianto, Ari (Biosaintifika: Journal of Biology & Biology Education, 2016)
Stelechocarpus burahol is one of the medicinal plants that contains flavonoids. The study was carried out to know flavonoid production of cultures in vitro S. burahol from mesocarp explants. Mesocarp explants were cultured on MS medium containing different combination and concentration of plant growth regulators i.e. picloram (5, 7.5 and 10 mg/L) and 2, 4-D (10, 15 and 20 mg/L) under dark condition. Induction of callus formation started on the 20.29th to the 29.86th days. Medium supplemented with Picloram and dark state proved to be the best condition for optimum callus induction from mesocarp explants of S. burahol. Callus grown on medium with the addition of 7.5 mg/l Picloram produces the highest flavonoid. The maximum production of the secondary metabolite was obtained from 8 weeks old callus. However, by the time of callus ageing, its output has declined. It could be concluded that callus cultures from mesocarp S. burahol can be used for flavonoid production.How to CiteHabibah, N. A., Moeljopawiro, S. Dewi, K. & Indrianto, A. (2016). Flavonoid Production in Callus Cultures from Mesocarp ofStelechocarpus burahol. Biosaintifika: Journal of Biology & Biology Education, 8(2), 214-221.